DONALD TRUMP’S “HATE SPEECH”? - Perez Martinez, Ramon Manuel (Cinzontle, 2023)
Frequently, and a certain lightness, it has been said that Donald Trump’s speech is a typical case of "hate speech", assuming its pathological and incoherent character. I don’t deny the value and truth of this cathegorization, but I question its usefulness in order to understand the magnitude and nature of the discourse of the president of the United States, capable of shaking the order of the world and the old ecumenical pretensions. In this way, instead of dwelling on the descriptions of the Trumpian discourse as a product of ignorance and resentment, here is proposed a rhetorical analysis that projects the evidence that we are dealing with wise and effective uses of old manipulation techniques perfectly thought out and with defined purposes, similar to those used by Adolf Hitler, for example, in the magnificent sense of opportunity, known since antiquity as Kairos.